E-181 Quantifying the extent of meningioma preoperative embolization through volumetric analysis: a retrospective case series. (23rd July 2022) - Faulkner, D; Feng, R; Bruhat, A; Kwon, F; Baker, T; Kellner, C; Mocco, J; Fifi, J; Shigematsu, T; Majidi, S; Shrivastava, R; Bederson, J; et al.
Abstract : Introduction: Endovascular embolization is an adjunct to surgical treatment of meningiomas. 1–4 There is controversy regarding the utility of preoperative tumor embolization, however, highlighted by one recent meta-analysis suggesting that endovascular embolization does not significantly improve patient outcomes. Preoperative embolization is most often used in an attempt to minimize blood loss during resection, but embolization has also been implicated in inducing tumor necrosis, reducing tumor volume, and leading to improvement in postoperative symptoms. 2, 5, 6 Direct, quantitative assessments of the efficacy of tumor embolization are lacking to date, however, given that embolization is almost universally followed by surgery. For this reason traditional measures of surgical outcome reflect a complex interaction of two procedures. Here we demonstrate the feasibility of direct assessment of extent of embolization through volumetric segmentation on pre- and post-embolization magnetic resonance imaging (MRI). Methods: Twenty-six consecutive patients who underwent preoperative meningioma embolization underwent an additional MRI after tumor embolization, prior to resection. MRI images were acquired on a 1.5T or a 3.0T scanner. Contrast-enhanced T1-weighted axial volumetric simulation images were used for analysis. Manual image segmentation was conducted with Slicer software (slicer.org). Embolization was quantified as the ratio of residual contrast-enhancing volume to post-procedure tumor volume. Percent embolization was computed as a voxel-based ratio obtained through digital volumetric analysis of the appropriate image sequences, and defined as low (<25%), medium (25–75%) or high embolization (>75%) efficacy. Results: Thirty-five percent of patients (9/26) showed low extent of embolization, 38% showed medium extent of embolization (10/26), and 27% (7/26) showed high extent of embolization. Average extent of embolization was 42.64% (SE 6.48%). No significant decrease in tumor tissue volume was observed immediately following embolization, with a cohort-wide mean reduction of 4.87% (p=0.118). Conclusion: This study demonstrates the feasibility of additional MR imaging prior to the resection of embolized tumors, enabling precise quantification of embolization extent prior to tumor removal. Embolization extent may play a role in determining the surgical utility of preoperative embolization, and may have an impact on parameters such as embolization-induced liquefactive tumor necrosis (and other factors related to resectability), as well as tumor-related intraoperative blood loss. Imaging and quantitative analysis may also lead to improved embolization techniques. Further studies are underway both to automate this process of embolization quantification and to enable the quantification of embolized tumors through other imaging modalities, such as angiography. Disclosures: D. Faulkner: None. R. Feng: None. A. Bruhat: None. F. Kwon: None. T. Baker: None. C. Kellner: None. J. Mocco: None. J. Fifi: None. T. Shigematsu: None. S. Majidi: None. R. Shrivastava: None. J. Bederson: None. S. Dunn: None. B. Rapoport: None.